Percutaneous Scaphoid Fixation: Experience Value among Different Approaches - Ramos-Marques, Nuno; Ferrão, Ana; Morais, Bruno; Barreira, Mariana; Teixeira, Frederico (Journal of Wrist Surgery, 2020)
Background Percutaneous scaphoid osteosynthesis is an attractive and increasingly popular option, as a treatment for acute scaphoid fractures in selected cases, and as an alternative to conservative treatment. The purpose of this study is to assess the radiographic positioning of the screw in percutaneous scaphoid fixation, taking into consideration the surgeons' experience, and the difference between volar and dorsal approaches.Methods We retrospectively assessed patients undergoing percutaneous scaphoid fixation from 2013 to 2019. Inclusion criteria are as follows: (1) scaphoid waist fractures (Herbert's B2), (2) a minimum of 18 years of age and a maximum of 55 years of age, (3) dominant hand, (4) manual work, (5) minimum follow-up time of 6 months, and (6) without associated lesions. Criteria for correct positioning are as follows: (1) on the axis or parallel to the scaphoid axis with a maximum deviation of 1.5 mm volar/dorsal, (2) without proximal/dorsal prominence, (3) correct scaphoid alignment/reduction, and (4) absence of threads in the fracture site. Radiographs were evaluated separately by a hand surgeon, a general orthopaedic surgeon, and an orthopaedic resident.Results With a total of 39 patients, a dorsal approach was performed in 10 patients and a palmar approach in 29 patients. We verified a very good interobserver reliability. The hand surgeon's team correctly positioned 15 (83.3%, 15/18), while the other team did 9 correctly (42.9%, 9/21). Comparing teams according to the approach used, the dorsal approach did not show a statistical difference, while the same was not true for the volar approach (p < 0.05).Conclusion This points to a positive impact on the team's experience in the positioning of the screws, and therefore in the benefit of treatment by teams dedicated to the area, while daring to suggest that less-experienced surgeons should utilize the dorsal approach.
Keywords: dorsal/volar approach; experience; percutaneous fixation; positioning; scaphoid fracture